Aktivitas Antioksidan dan Stabilitas Ekstrak Andaliman (Zanthoxylum acanthopodium DC) Terhadap Panas, Cahaya Fluoresen dan Ultraviolet - Edi Suryanto; Sri Raharjo; Hardjono Sastrohamidjojo; Tranggono Tranggono (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2005)
Andaliman fruit is seasoning commonly used in traditional food preparation of North Sumatera. The objectives of this study were to determine the antioxidant stability of andaliman extract on high temperature fluoresence and ultraviolet high exposures. Andaliman fruit was sequentially extracted with hexane, acetone and ethanol. Antioxidant activity of each extracts at 50-500 ppm level are evaluated in 1,1-dipheny1- 2-picodhydrazyl (DPPH) radical 'decoloration test. The third extract was evaluated on heating at Iwo high temperature exposures were conducted on the third extract: storage at 100°C for 15, 30, 60, and 120 minute and storage at 100, 120, 140 and 180.c for 60 minutes. The treatment of light exposure were under 4000 lux fluoresen light and ultraviolet C (200-280 nm) light for 5 hours. The effect of ethanol extract (ESHAE) and acetone extract (ESHA) extract showed the highest scavenging activity in 1,1-dipheny1-2-picrylhydrazyl (DPPH) radical, followed acetone and hexane extract. BHT and atocopherol as positive control had weaker radical scavenging activity in DPPH system. Ethanol extract (ESHAE) extract at 200 ppm was significantly possessed high stability on heating at 100°C, fluoresent and ultraviolet, whereas hexane extract (EH) was low antioxidative efect. The addition of ethanol extract (EHSAE) at different concentration exhibited excellent reduction power more than acetone extract (ESHA) and hexane extract (EH). Ethanol extract (ESHAE) at concentration 500 ppm showed equal with 200 ppm BHT and rutin, but more than a-tocopherol. It is concluded that the ESHA and ESHAE extract of andaliman fruit showing stability on heating a! /00°C for 60 minutes, fluoresent and ultraviolet light light during 5 hours